Sierra Leone : Social Protection Assessment - World Bank (Washington, DC, 2014)
The objective of this assessment is to respond to the government's call for analytical work to guide the development of an improved social protection system. Its goal is to help the government to put the social protection policy into action and to provide an analytic underpinning for the social protection pillar of the Agenda for Prosperity. The basis of the assessment is provided by the concept of social risk management (SRM), which was developed by the World Bank in the early 2000s, and the assessment uses the lifecycle (or life-course) analysis. Chapter one discusses the main risks facing families in Sierra Leone and the conceptual framework of this assessment. Chapter two identifies the country's main vulnerable groups, discusses the principal risks faced by these groups and by households in general, and estimates the number of individuals or households that are at risk. Chapter three reviews the principal programs that are already in place to address the risks that have been identified. Chapter four assesses the adequacy of the social protection system by analyzing: spending; program coverage, gaps, and overlaps; benefit generosity; targeting mechanisms and beneficiary incidence; cost-effectiveness; monitoring and evaluation; and institutional arrangements and participation. Chapter five contains recommendations. The complexity of building social protection systems should not be underestimated. It entails many different actors, preferences, programs, policies, instruments, institutions, and financing, and it often involves difficult trade-offs. The pace at which any social protection system is developed must therefore be in line with the country's institutional and financial conditions and capabilities.